Cycling uphill and downhill - Swain, D. P. (Sportscience)
Cycling is a complex sport in which competitors must contend with a variety of strategies employed by opponents as well as many environmental factors. Chief among the latter is the hilliness of the terrain. Performance on hills is a primary factor in determining success in the major international cycling competitions. In this article I present a review of current scientific knowledge related to cycling up and down hills and describe what athletes can do to improve their performance on hills. Summary: The primary forces a cyclist must overcome are air resistance and gravity. Air resistance increases exponentially with speed. In the transition from cycling on a flat road to climbing a hill, the decreased speed reduces air resistance to the point where drafting other riders provides little benefit. At this point, smaller cyclists, who tend to have superior power-to-weight ratios, will be able to break way from the peloton. Climbing ability can be enhanced by minimizing weight, and also by pedaling at a consistently high cadence. Large cyclists can achieve greater downhill speeds, but on hilly courses smaller cyclists still have an advantage. Using a variable power strategy enhances overall performance: increasing effort slightly on uphills and compensating with decreased effort on downhills. On steep descents it is necessary to pedal only at the start and when coming out of turns to achieve terminal velocity quickly.